Single molecule atomic force microscopy studies of photosensitized singlet oxygen behavior on a DNA origami template - Helmig, Sarah; Rotaru, Alexandru; Arian, Dumitru; Kovbasyuk, Larisa; Arnbjerg, Jacob; Ogilby, Peter R.; Kjems, Jorgen; Mokhir, Andriy; Besenbacher, Flemming; Gothelf, Kurt V. (Acs Nano, 2010)
DNA origami, the folding of a long single-stranded DNA sequence (scaffold strand) by hundreds of short synthetic oligonucleotides (staple strands) into parallel aligned helices, is a highly efficient method to form advanced self-assembled DNA-architectures. Since molecules and various materials can be conjugated to each of the short staple strands, the origami method offers a unique possibility of arranging molecules and materials in well-defined positions on a structured surface. Here we combine the action of light with AFM and DNA nanostructures to study the production of singlet oxygen from a single photosensitizer molecule conjugated to a selected DNA origami staple strand on an origami structure. We demonstrate a distance-dependent oxidation of organic moieties incorporated in specific positions on DNA origami by singlet oxygen produced from a single photosensitizer located at the center of each origami. © 2010 American Chemical Society.